Zakres podmiotowy prawa do nauki osób niepełnosprawnych - Gajewska, Kinga (Wydawnictwo Uniwersytetu Rzeszowskiego, 2026)
Artykuł ma na celu omówienie zagadnień konstytucyjnoprawnych związanych z zakresem podmiotowego prawa do nauki w Polsce. Autorka skupiła się na konstytucyjnych regulacjach związanych z prawem do nauki obywateli, w szczególności w kwestii związanej z dostępem do edukacji osób z niepełnosprawnościami. Jednym z celów opracowania jest określenie roli czynników prawnych, politycznych, społecznych w procesie urzeczywistniania konstytucyjnego prawa do nauki.

The article aims to discuss constitutional issues related to the scope of the subjective right to education in Poland. The author focuses on constitutional regulations concerning the right to education for citizens. It also addresses the education of people with disabilities, foreigners, national and ethnic minorities, as well as the education of Polish citizens living abroad. It analyses the availability of the right to education for different social groups.
The subjective scope of the right to education
Keywords: prawo; nauka; prawo podmiotowe; obywatele; osoby niepełnosprawne; law; education; subjective right; citizens; people with disabilities; foreigners; national minorities; ethnic minorities